2022
DOI: 10.3389/fnins.2022.1007571
|View full text |Cite
|
Sign up to set email alerts
|

Supportive psychological therapy can effectively treat post-stroke post-traumatic stress disorder at the early stage

Abstract: Post-traumatic stress disorder (PTSD) can develop after stroke attacks, and its rate ranges from 4 to 37% in the stroke population. Suffering from PTSD not only decreases stroke patient’s quality of life, but also relates to their non-adherence of treatment. Since strokes often recur and progress, long-term medical management is especially important. However, previous studies generally focused on the epidemiological characteristics of post-stroke PTSD, while there are literally no studies on the psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The literature on specifically treating PTSD in a post-stroke population is now showing some progress. Jiang et al conducted a randomized controlled trial on 170 first-ever stroke patients and provided modest evidence that supportive psychological therapy can effectively treat post-stroke PTSD in its early stages [99]. A recent case report also showed clinically significant resolution of PTSD symptoms following three sessions of eye movement desensitization and reprocessing therapy [100].…”
Section: Strokementioning
confidence: 99%
“…The literature on specifically treating PTSD in a post-stroke population is now showing some progress. Jiang et al conducted a randomized controlled trial on 170 first-ever stroke patients and provided modest evidence that supportive psychological therapy can effectively treat post-stroke PTSD in its early stages [99]. A recent case report also showed clinically significant resolution of PTSD symptoms following three sessions of eye movement desensitization and reprocessing therapy [100].…”
Section: Strokementioning
confidence: 99%
“…Furthermore, a large epidemiological study demonstrated that women with PTSD had an increased risk of ectopic pregnancy, spontaneous abortion, premature delivery, and fetal overgrowth (12). Effective management of PTSD can be achieved through psychological and pharmacological interventions (13,14). To reduce or prevent the occurrence of PTSD, it is important to provide psychological intervention to adolescent patients who have undergone induced abortion.…”
Section: Introductionmentioning
confidence: 99%